1997
DOI: 10.1161/01.atv.17.7.1303
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Hypercholesterolemia and Ox-LDL on Angiogenesis-like Endothelial Growth in Rabbit Aortic Explants

Abstract: Hypercholesterolemic (HC) rabbits exhibit suppressed compensatory vascular growth after restriction of arterial supply. However, neovascularization is commonly found in atheromas containing inflammatory cells. We used an in vitro model to determine the effects of hypercholesterolemia on angiogenesis in the absence or presence of inflammatory cells. HC rabbit aortic explants (1 mm2) with or without (n = 90 each) lesion-forming inflammatory cells were cultured in a collagen matrix with serum-free medium. Explant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 41 publications
6
54
1
Order By: Relevance
“…The latter phenomenon is in keeping with several previous studies. [21][22][23] The oxLDL treatment of HCAECs was associated with a concentrationdependent expression of LOX-1 as shown earlier. 25 Pretreatment of cells with a specific anti-LOX-1 antibody blocked the angiogenic response, suggesting that oxLDL induces tube formation from HCAECs via LOX-1 upregulation.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The latter phenomenon is in keeping with several previous studies. [21][22][23] The oxLDL treatment of HCAECs was associated with a concentrationdependent expression of LOX-1 as shown earlier. 25 Pretreatment of cells with a specific anti-LOX-1 antibody blocked the angiogenic response, suggesting that oxLDL induces tube formation from HCAECs via LOX-1 upregulation.…”
Section: Discussionsupporting
confidence: 60%
“…In contrast to the ability of small concentrations of oxLDL to stimulate tube formation, higher concentrations of oxLDL (10, 20, 40 g/mL) were noted to inhibit cell growth and cause cell injury in accordance with previous observations. [21][22][23][24] We also used native-LDL as a negative control, and found that native LDL (5 g/mL) had no effect on tube formation. Based on these findings, we chose the maximum effective concentration of oxLDL (5 g/mL) for subsequent experiments.…”
Section: Results Oxldl and Tube Formationmentioning
confidence: 99%
“…Furthermore, growth factors other than vascular endothelial growth factor can also be involved in atherogenesis, which complicates the interpretation of the results. 27,28 In the present study, we did not address the effects of FTS on endothelial cell function in this atherosclerosis model.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, increases in age or hypercholesterolemia are associated with reduced angiogenesis. 15,16 Moreover, clinical data suggest a relation between impaired coronary blood flow regulation and risk A, EPCs were isolated from peripheral blood from 28 patients with CAD and 9 age-matched control subjects, and VEGF-stimulated migration was determined with a modified Boyden chamber. B through E, Number of migrating EPCs from 28 patients with CAD and 9 age-matched healthy volunteers was correlated with total number of risk factors (B) and individual risk factors (C through E).…”
Section: Discussionmentioning
confidence: 99%